Temporal Analysis of Heat Waves and Cold Waves for Samsun Province - Sena Güneş; Bahtiyar Efe (Doğal Afetler ve Çevre Dergisi)
In this study, temporal analysis of heatwaves and cold waves has been made for Samsun province. Within the scope of the study, the maximum and minimum temperature data obtained from Samsun city centre and Bafra meteorology stations located are used. In the study, the 90th percentile of maximum air temperatures for each season are calculated and used as threshold to detect the heat waves by using the R program. The 10th percentile of minimum air temperatures for each season are calculated and used as threshold to detect the cold waves. The lasting of the maximum air temperatures above the 90th percentile for at least five consecutive days is described as a heat wave. The lasting of the minimum air temperatures below the 10th percentile for at least five consecutive days is described as a cold wave. It has been calculated that the number of heat waves in Samsun and Bafra has decreased towards the last years, and the number of cold waves has decreased towards the last years. The average duration of heat waves increases for both stations in all seasons. The duration of cold air waves has decreased except for the autumn season for both stations. In the autumn season, the duration of cold air waves has increased at both stations.